Non Traumatic Acute Abdominal pain (100 days study in Emergency Department) - Atiyah, Taqi Saadoon (AL-Kindy College Medical Journal, 2019)
Background: Abdominal symptoms are possibly the most frequent of all symptoms encountered in surgical practice.  Pain is the most common of all abdominal symptoms.  Causes of acute abdominal pain include both medical and surgical. Most symptoms arise from intra-abdominal organs or systems while some may originate extra abdominally and are then referred to the abdomen. Medical causes of abdominal pain are encountered more frequently.Objective: To study the causes of acute abdominal pain in patients attending emergency department in Al- Imamain Al- Kadhimain Medical City.Type of the study: A prospective cross sectional studyMethods: The patients attending Emergency Department in Al- Imamain Al- Kadhimain Medical City over the period from April-2014 to April 2016. There was a one day call duty per week managed by the same surgical team (total one hundred days study). Onlypatients above 12 years old with acute non-traumatic abdominal pain were included in this study.Results: The total number was 1217 patients over hundred days study. Their age ranges from 12-83 years; average age was 36.18 ±17 year. There was slight female predominance, 638 (52.42%) female patients and 579 (47.58%) male patients.  The most common cause of abdominal pain was acute appendicitis 252 (20.70%), followed by ureteric colic 251 (20.62%), and acute cholecystitis249 (20.46%). Conservative management was done for 836 (68.69%) patients, while operative management done for 379 (31.14%) patients.  Postoperative mortality was 8 (2.11%) patients.Medical causes of acute abdominal pain were found in 48 (5.74%) patients.Conclusion: Not all the patients attending surgical emergency department needs operations. Causes of acute abdominal pain include both medical and surgical diseases, some of the medical diseases are very serious like acute viral hepatitis, myocardial infarction , and diabetic ketoacidosis; and should not submit those patients to unnecessary operations with serious and may be fatal postoperative complications. General urine examination is a must in all patients with acute abdominal pain. Electrocardiography (ECG) may be needed in old patients.